2014
DOI: 10.1021/ma5006638
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Unentangled cis-1,4-Polyisoprene Confined to Nanoporous Alumina

Abstract: The dynamics of unentangled cis-1,4-polyisoprene confined within self-ordered nanoporous alumina (AAO) is studied as a function of molecular weight (5000–300 g/mol) and pore size (400–25 nm) with dielectric spectroscopy. The main effects are the pronounced broadening of both segmental and chain modes with decreasing AAO pore diameter. This suggests that the global chain relaxation is retarded on confinement. Remarkably, the distribution of relaxation times is broadened even within pores with size 50 times the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
116
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(127 citation statements)
references
References 46 publications
9
116
1
1
Order By: Relevance
“…All these effects are similar to results reported for PNCs. [17][18][19][20][21] The inset of Fig.3 shows the temperature dependence of the alpha relaxation time estimated from the peak position of the loss spectra ω peak (τ α = 1/(ω peak )). Good agreement between our measurements and literature data 55 indicate our samples are free of solvent from sample preparations.…”
Section: Resultsmentioning
confidence: 99%
“…All these effects are similar to results reported for PNCs. [17][18][19][20][21] The inset of Fig.3 shows the temperature dependence of the alpha relaxation time estimated from the peak position of the loss spectra ω peak (τ α = 1/(ω peak )). Good agreement between our measurements and literature data 55 indicate our samples are free of solvent from sample preparations.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristic time τ for the slow process was found to exhibit a very strong dependence on molecular weight, τ ∼ M w 5.7 , which could be eliminated by coating the CPG (controlled porous glass) with a silane that prevented adsorption. Floudas et al 44 also reported broadened normal and segmental mode spectra from dielectric loss data of unentangled PI confined in nanoporous alumina. On the basis of these observations, the authors argued that confinement of even unentangled chains produces a broader distribution of relaxation events than in their unconfined and unentangled analogues.…”
Section: ■ Introductionmentioning
confidence: 94%
“…For polymeric fluids, the polymer chains near the inner wall can be strongly adsorbed. There exist experimental evidences for that from dielectric spectroscopy measurements for polymers confined to nanoporous alumina . These immobile chains create a “dead zone” of thickness Δ R .…”
Section: Theoretical Considerationsmentioning
confidence: 99%